Speciality 05.25.03 “Library science, bibliography and book science”. What are the prospects? - Valentina V. Brezhneva; Margarita Ya. Dvorkina; Olga A. Kalegina; Natalya V. Lopatina; Yuri N. Stolyarov (Библиосфера, 2020)
The material presents the views of the chairs and members of the dissertation councils at the KazGIK, MGIK, SPGIK and RSL on the specialty 05.25.03 indicated in the title on four issues: 1. Are you confident in the future of your dissertation council? What is your confidence or anxiety related to? 2. What do you think are the problems of modern library science, bibliography and book studies? 3. There are only 4 dissertation councils on the specialty – 03.25.03 – in Russia: in Kazan, Moscow, St. Petersburg, Khimki. Do you think this is sufficient for the development of our industry? 4. What question (s) on the dissertation council would you like to be asked?The answers showed concern for the future of not only of dissertation counsils as such, but confirmed serious concerns about the future of the specialty 05.25.03.